PWE-023 Could Faecal Immunochemical Tests for Haemoglobin (FIT) Change Surveillance of People with Intermediate Risk Adenomas?. (4th June 2013) - Kralj-Hans, I; Martin, J; Pearson, S; Piggott, C; Bowyer, H; Vart, G; Wagner, C von; Wardle, J; Halloran, S; Atkin, W
Abstract : Introduction: The NHS Bowel Cancer Screening Programme (BCSP) in England uses a biennial guaiac faecal occult blood test and identifies intermediate risk (IR) adenomas in approximately 5, 000 people a year who are then offered colonoscopic surveillance. A non-colonoscopic approach to surveillance in this group may be an attractive alternative which could reduce demand on this expensive and limited resource. Methods: In the 'FIT for Follow-Up' study we aim to determine the three-year programme sensitivity of annual FIT for detection of advanced adenomas (an adenoma > 10 mm, or one with tubulovillous or villous histology, or with high grade dysplasia) or colorectal cancer (CRC), using surveillance colonoscopy as the reference standard. Eligible participants are people aged 60–71 years, who have recently been diagnosed with IR adenomas in the BCSP, and are awaiting their first surveillance colonoscopy at three years. They are invited to complete a FIT test (Eiken Chemicals, Inc.) annually in the three year interval between screening and surveillance colonoscopy. Those who test positive (> 200 ng haemoglobin/mL buffer; OC Sensor) are offered immediate colonoscopy; those who test negative are offered another FIT test a year later. In total, eligible participants could complete three FIT tests prior to their first surveillance colonoscopy. Our sample size is 5, 200 participants completing a FIT test within a year of their screening colonoscopy. The study will also assess the acceptability and cost-effectiveness of annual FIT as an alternative to three-yearly surveillance colonoscopy. Results: In the first 10 months of the study, 2, 512 people (65.5% men) consented to take part and completed their first FIT test. The positivity rate in this group is 5.4% (6.1% in men and 3.3% in women) and only 7% of people testing positive declined to have their three-year surveillance examination brought forward. In FIT positive subjects who underwent colonoscopy, 24.7% had advanced adenomas and one participant had a cancer in the proximal colon. Virtually all study participants were satisfied with their experience of completing their first FIT kit (95.8%), and would be happy to do so again (94.7%). The majority of participants (over 80%) believed that participating in the study had reduced their chances of having bowel cancer. Conclusion: At this early stage in the study we can report that FIT is well accepted by participants and the yield at colonoscopy in those testing positive is high. Disclosure of Interest: None Declared.